Assessment of risk factors and prediction of premature ovarian failure - L. V. Tkachenko; I. A. Gritsenko; K. Yu. Tikhaeva; N. I. Sviridova; I. S. Gavrilova; V. A. Dolgova (Акушерство, гинекология и репродукция, 2022)
The problem of premature ovarian failure (POF) is currently in the spotlight of obstetricians and gynecologists worldwide. Early diagnosis of this pathology is necessary to prevent the development of serious pathological conditions. The systematization of modern ideas about laboratory and instrumental methods for POF diagnosing, assessing diagnostic value of parameters such as follicle stimulating hormone, anti-Mullerian hormone as well as the count of antral ovarian follicles, intraovarian blood flow and ovarian volume using ultrasound techniques, which can then be used as prognostic criteria for POF comprise a very important modality. Based on the findings obtained, early detection may lead to proposing new prognostic strategies.